A career in phonetics, applied linguistics and the public service. (5th June 2013) - Little, David; King, Lid
<x content-type="archive" xml:space="preserve">Abstract</x> As this issue was in preparation, the journal learned with great regret of the passing of John Trim. John was a long-serving member of the Language Teaching Board and his insight and advice proved invaluable for this and previous editors. An expert in the field of phonetics, linguistics, language didactics and policy, John worked tirelessly to improve the state of language teaching throughout his life. Among his key posts, he was director of the Council of Europe's Modern Languages Projects from 1971 to 1997 and supervised significant developments in language learning and teaching, including the Threshold Level and the Common European Framework of Reference. As a tribute to the man and his work, we are publishing in this and a subsequent issue one of the last interviews John gave, where he looks back with his customary perspicacity at one of the most exciting periods of change in the teaching and learning of foreign languages.